ANALISIS PERSEPSI KUALITAS SIARAN, FORMAT SIARAN TERHADAP BRAND AWARENESS DAN TERHADAP LOYALITAS PENDENGAR (STUDI KASUS RADIO PRAMBORS SEMARANG) - Adittama, Mugi; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2015)
Radio is a medium that has a range of selective solid segment and able to answer the need to ensure that communication can spur a change masyarakat.Radio has some powers because it can reach a large number of target audience at the same time, quickly deliver the message so that it can provide the most current information and easy to understand, it also provides a form of entertainment that radio.This study aims to identify and analyze the effect on the Listener Loyalty Radio Geronimo Semarang.Variabel company is bound by an intervening variable Listener Loyalty Brand Awareness. the independent variable is the perception of quality of broadcasting and rerunning Format. The samples were 400 young people in the City Semarang.Data used is primary data obtained through kuesioner.Alat analysis used multiple linear regression.The study concluded that radio listeners can earn loyalty backed by a factor of a positive perception of the broadcast quality of the Listener Loyalty and pulled positively to the broadcast format Listener Loyalty. It is also supported by a positive factor for Brand Awareness Listener Loyalty.